Perception of Economics Instruction on Technology Instruments to Face the Pandemics Covid-19 - Phousith Phongsavath; Rika Andriani; Zuhri Saputra Hutabarat (Universitas Batanghari Jambi, 2022)
This study aims to analyze the readiness of the economics lecturers and students at the Faculty of Economics and Business Management, National University of Laos, Laos in providing an economics education via the online application to face the pandemics Covid-19. The approach in this research uses a qualitative descriptive approach with the type of case study research. The informants of this study were economics lecturers and students, who were selected through the purposive sampling technique. This study indicates that the process of economics students consists of understanding, preparation, instrument tools, and online application relevant cases. This study aims to improve and find the solution to the quality of economics students in facing the pandemics Covid-19. The finding shows that most of the economics lecturers and learners are readiness, well understand and familiar utilizing with the online application.